2020
DOI: 10.1007/s11666-020-01056-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Residual Stress Measurements Conducted by X-ray Stress Analysis and Incremental Hole Drilling Method

Abstract: The level of residual stresses is of great importance for many applications. In this work, the two established residual stress analysis methods x-ray stress analysis and incremental hole-drilling combined with electronic speckle pattern interferometry are compared. Each stress analysis method has its specific limitations. Furthermore, the residual stress state of a material is influenced by its processing history. To compare both methods, aluminum-based specimens (AlCu6Mn, AlZn5.5MgCu) with different processin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The literature presents the application of CS for AM for a large number of materials, highlighting the components made from 316L stainless steel [ 10 , 11 , 12 , 13 , 14 ], Cu alloys [ 15 , 16 , 17 ], and Ti alloys [ 18 , 19 , 20 , 21 ], but not limited to them since Al alloys [ 21 , 22 , 23 , 24 ], Ni superalloys [ 25 , 26 ], maraging steel [ 27 , 28 , 29 ], and many others have also been studied. Moreover, these CSAM components have interested different sectors, such as aerospace, automotive, energy, medical, and marine sectors, among others [ 8 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The literature presents the application of CS for AM for a large number of materials, highlighting the components made from 316L stainless steel [ 10 , 11 , 12 , 13 , 14 ], Cu alloys [ 15 , 16 , 17 ], and Ti alloys [ 18 , 19 , 20 , 21 ], but not limited to them since Al alloys [ 21 , 22 , 23 , 24 ], Ni superalloys [ 25 , 26 ], maraging steel [ 27 , 28 , 29 ], and many others have also been studied. Moreover, these CSAM components have interested different sectors, such as aerospace, automotive, energy, medical, and marine sectors, among others [ 8 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…As is wellknown, the decrease in compressive residual stress of the perovskite lm will increase the crystal lattice spacing, which means that the grain number in the same deposition area decreases while the grain size increases. [46][47][48] In our results, the reduced compressive residual stress in [PNA]BF 4 treated lm makes the crystal lattice spacing increase, leading to the enlargement in grain size. This in turn is beneted from the uniform crystallization of Sn-/Pb-component perovskite crystals and promotes high crystalline quality of the perovskite lm.…”
Section: Chemical Anchoring Effect Based On [Pna]bf 4 Treatment In Sn...mentioning
confidence: 56%
“…The stress was the smallest in the middle and gradually increased to both sides in both vertical and horizontal directions. Bobzin et al [74] measured the residual stress distribution along the depth direction of the aluminum-based coating of the steel structure by the drilling method and found that the heat treatment had a relaxation effect on the residual stress level of the coating. Mohamed et al [75] measured the residual stress of stainless steel coatings with different thicknesses by the drilling method.…”
Section: Stress Detectionmentioning
confidence: 99%